THE IMPORTANCE OF ANIMAL PROTEIN FULFILLMENT FOR OPTIMAL GROWTH OF UNDER-5 CHILDREN: MECHANISTIC INSIGHTS AND CLINICAL IMPLICATIONS - Rahayu Kania; Dessy Pratiwi; Nurfadilah M Rajab (Journal of Indonesian Specialized Nutrition, 2026)
Background: Protein plays a fundamental role in growth regulation through its structural, metabolic, and signaling functions. Increasing evidence indicates that the consumption of animal-source foods is associated with improved linear growth and a reduced risk of stunting during infancy and early childhood. This review aimed to evaluate the contribution of animal protein intake to linear growth among children under five years of age. Methods: A literature review was conducted to synthesize current evidence from studies indexed in PubMed and Scopus between 2016 and 2026. Eligible publications included observational studies, randomized controlled trials (RCTs), and review articles that examined the relationship between animal protein intake and indicators of linear growth in children younger than five years. Results: Animal-source proteins, including those derived from fish, eggs, milk, and meat, were consistently associated with favorable linear growth outcomes during the first five years of life. Evidence from randomized trials and meta-analyses demonstrated modest but significant improvements in length-for-age z-scores (LAZ), while cohort studies reported lower stunting prevalence among children with higher animal-source food consumption. Nevertheless, the magnitude of these effects varied according to contextual factors, including dietary adequacy, maternal nutritional status, infection burden, and environmental conditions. Conclusion: Regular consumption of modest amounts of animal-source foods can contribute to measurable improvements in linear growth, with pooled evidence indicating significant benefits across low- and middle-income countries. However, the effectiveness of animal protein interventions is optimized when integrated with strategies addressing underlying determinants of growth.